Population and Social Demographic Poverty: A Case Study in the Border Areas of East Kalimantan and North Sulawesi - Ade Latifa; Aswatini Aswatini; Haning Romdiati (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2008)
This paper discusses the social-demographic dimensions of poverty and is based on findings from a four-year research program (20069) conducted by PPKLIPI in the border areas of East Kalimantan and North Sulawesi. The general objective of this study is to develop methods for measuring poverty using social-demographic variables: fertility, mortality, migration, education, marriage and occupation. This research used quantitative and qualitative approaches. The intention in using these two approaches was to enable comprehensive data to be gathered on multidimensional aspects of social-demographic poverty. The quantitative data were collected by using survey techniques; a sample of 400 households was taken from each area. Qualitative data were obtained from in-depth interviews, focus group discussions, observation and desk reviews. The findings show that some socialdemographic variables are likely to be related (correlate) to household poverty; such variables as mean years of schooling of household members aged 15 years and above (below six years of education), the number of children born to the household (more than two) and children below five years of age who had died in the household. The regression results (factor analysis) reveal that about 43.1 per cent and 49 per cent of households are categorised as poor households in the border areas of East Kalimantan and North Sulawesi respectively.